Appropriate antibiotic prescribing in Community-Acquired Pneumonia in a Norwegian hospital setting - Høgli, June (UiT The Arctic University of Norway, 2015)
The papers of this thesis are not available in Munin. Paper I. MAT-CAP: a novel medication assessment tool to explore adherence to clinical practice guidelines in community-acquired pneumonia. Høgli JU, Småbrekke L, Garcia BH. Available in Pharmacoepidemiology and Drug Safety 2014; 23: 933–941 Paper II. Adherence to guideline for empirical antibiotics is safe and reduces risk of readmission of hospitalised patients with community-acquired pneumonia in Norway. Høgli JU, Garcia BH, Svendsen K, Skogen V, Småbrekke L. (Manuscript) Paper III. An audit and feedback intervention study increased appropriate antibiotic prescribing at a Norwegian hospital. Høgli JU, Garcia BH, Skjold F, Skogen V, Småbrekke L. (Manuscript) Appropriate antibiotic prescribing is associated with favourable levels of antimicrobial resistance and clinical outcomes. Literature has indicated that antibiotic treatment of hospitalised patients with community-acquired pneumonia (CAP), the leading cause of death due to infection in adults worldwide, have potential for improvement. The overall aim of this PhD-work has been to promote appropriate antibiotic prescribing in hospitalised patients with CAP. We have developed and validated a Medication Assessment Tool for CAP (MAT-CAP) for retrospective audit of antibiotic prescribing at the University Hospital North Norway (UNN). Consequently, using this tool, areas with low and high quality of prescribing can be identified. Further, we have explored the association between adherence to Norwegian guideline recommendations and mortality, risk of readmission and prolonged length of stay for inpatients with CAP. We identified that adherence to guideline on empirical antibiotic was high, safe and associated with reduced risk of readmission to hospital within 30-days in a selective group of CAP-patients admitted to UNN. Our findings support the Norwegian guideline recommendations, and demonstrate the importance of having guidelines adapted to local and national levels of antimicrobial resistance. Third, in an ...